KETOPROFEN-CARBOXYMETHYL CHITOSAN MICROPARTICLES PREPARED BY IONIC CROSSLINKING - SPRAY DRYING : OPTIMIZATION AND EVALUATION - Sari, Retno; Sari, Retno (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The aim of this research was to investigate the effect of two operating parameters (inlet temperature and pump speed) of laboratory spray dryer to optimize the production of ketoprofen-carboxymethyl chitosan (CM chitosan) microparticles and the effect of carboxymethyl chitosan concentration on microparticles characteristics. Methods: Microparticles with various concentration of CM chitosan were prepared by ionic gelation with CaCl2, then dried by spray drying with various inlet temperature and pump speed. The obtained microparticles were evaluation for particle size, drug entrapment efficiency and drug release. Results: The results showed that inlet temperature at 100Â°C and pump speed at 9.0 ml/min was known to be the optimum condition since the drying process was relatively faster and it could produce the most yield. The obtained CM chitosan microparticles have irregular and hollow shape with the size of 1.1 â€“ 2.1 Î¼m. As carboxymethyl chitosan concentration increased, mean particle size and drug entrapment efficiency of the drugs increased. In simulated intestinal fluid media pH 6.8, the release rate of ketoprofen from microparticles was delayed up to 0.43 times slower than ketoprofen powder. Conclusion: The optimal condition for spray drying in this study was at pump speed 9.0 ml/min with inlet temperature 100Â°C, since it gave the most yield compare to other conditions. The size of ketoprofen-CM chitosan microparticles were between the range of 1.1 â€“ 2.1 Î¼m with high drug entrapment. In general, microparticles of CM chitosan could delay ketoprofen release in simulated intestinal fluid media. Keywords: Microparticles, Spray drying, Ketoprofen, Carboxymethyl chitosan.